Introducing design thinking in hindi foreign language education: an innovative approach for enhancing holistic proficiency (Journal of Oriental Studies, 2019)
Abstract. The vast changes of the 21st century have greatly contributed to our life. Technological advancement, internet, instant information, globalization and wider connectivity have provided us better facilities on the one hand and created problems and challenges on the other hand that are different from the previous one. The traditional methods and approaches are no longer sufficient and adequately effective to solve the problems emerged out of the changed environment of 21st century which is moving fast towards the artificial intelligence revolution. Like other walks of our life, this changing paradigm has influenced the education also. Consequently, new insights have led to the discovery of new methods and new approaches to deal with the problems and challenges before us. Design Thinking is one of those approaches that originated in the field of architecture, but being effective for problem solving, it is found to be useful in education also. Nowadays, students’ preferences, their learning objectives and learning tools have entirely changed. In the wake of present circumstances, pedagogical mindset, teaching approach and method needs to be revolutionized through integrating innovative ideas in education. Due to its human-centered approach, Design Thinking can be an important tool in this direction towards solving complex learning problems. Design Thinking has been brought in school education and has yielded better results. It has also been introduced in foreign language education. I believe that the method and approach of design thinking should be introduced in Hindi foreign language education (HFLE) as well. This paper explores possibilities of introducing Design Thinking in HFLE for enhancing holistic proficiency of learners. Key words: Design Thinking, Wicked problems, Analytic, Synthetic, Creativity, Innovation, Collaboration.